2011
DOI: 10.5001/omj.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Non Allergic Rhinitis: Prevalence, Clinical Profile and Knowledge Gaps inLiterature

Abstract: The study found that more than half of rhinitis patients suffered from NAR. There are no specific diagnostic tests for NAR; a thorough case history is the best diagnostic tool to date. A substantial knowledge gap exists in literature with relations to pathogenesis, clinical and laboratory diagnosis, as well as in reference to medical and surgical outcomes. Larger studies are required and management outcomes need to be studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…19,20 In our study, the prevalence for specialist tertiary care setting was found to be 7%, which compared to the prevalence of NAR given in the literature is lower. 4 We found the prevalence of perennial AR was much higher (84%) compared to seasonal AR (16%). One reason could be the geographical and topographical features leading to lack of vegetation and pollen in Oman's desert terrain, the same factors explain the low prevalence of seasonal AR.…”
Section: Discussionmentioning
confidence: 85%
“…19,20 In our study, the prevalence for specialist tertiary care setting was found to be 7%, which compared to the prevalence of NAR given in the literature is lower. 4 We found the prevalence of perennial AR was much higher (84%) compared to seasonal AR (16%). One reason could be the geographical and topographical features leading to lack of vegetation and pollen in Oman's desert terrain, the same factors explain the low prevalence of seasonal AR.…”
Section: Discussionmentioning
confidence: 85%
“…In chronic or recurrent paranasal sinus disease, MSCT is used both as a diagnostic tool to identify anatomical anomalies and mucosal pathology and as a preoperative map to guide the surgeon prior to endoscopic sinus surgery. Ostiomeatal complex is the key area in the pathogenesis of chronic or recurrent sinusitis; many anatomic variations may affect this region and may play an important role in the obstruction of the ostiomeatal complex [ 5 ]. One of the prerequisites for successful FESS is knowledge of the complex anatomy of paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…The reported frequency of anatomic variations in patients with chronic rhinosinusitis is as follows: agger nasi cells in 15%, Haller cells in 7%, conchae bullosa in 30%, paradoxical middle turbinate in 24%, and septal deviation in 21% of patients [ 5 ]. Outcomes of FESS for chronic rhinosinusitis depend on an accurate evaluation of the disease and paranasal anatomic variations.…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of universal terminology of NAR and, in particular its phenotype using objective criteria, remain the most striking gaps in our knowledge at present (16) .…”
Section: Introductionmentioning
confidence: 99%